Tuning band gaps and optical absorption of BiOCl through doping and strain: insight form DFT calculations. Issue 31 (26th July 2017) - Zhang, Le; Tang, Zhen-Kun; Lau, Woon-Ming; Yin, Wen-Jin; Hu, Shu-Xian; Liu, Li-Min
Abstract : Doping and strain were used to tune the electronic structures and optical properties of BiOCl using first principle calculations. Abstract : Bismuth oxyhalides (BiOX, X = Cl, Br, and I) are a new family of promising photocatalysts. BiOCl and BiOBr possess large band gaps and weak absorption in visible light regions, which limit their applications. Although the band gap of BiOI is suitable to absorb most of the visible light, its redox capability is very weak. In this work, the doping and strain effects on the electronic structures and optical properties of BiOCl are explored using first principle calculations. The results show that doping in BiOCl, especially co-doping of Sb and I atoms, can obviously decrease the band gaps along with enhancing the optical absorption coefficients of pristine BiOCl because of the electronegativity difference between Sb/I atoms and Bi/Cl atoms. Meanwhile the band gap of BiOCl can be tuned under strain. This work offers potential strategies to enhance BiOCl absorption coefficients in the visible light region and its photocatalyst activity.